Aspiration and Self-Realization: The Ameliorative Projects of Steve Biko. Issue 2 (March 2023) - Gray, David Miguel
Work on the conceptual amelioration of race concepts is usually negative or critical: it uncovers social features that contribute to racial hierarchies. Much less focus has been placed on how ameliorative accounts contribute to positive change. Using an account of race developed by Steve Biko during South African apartheid, I will argue that we can extract a novel account of positive amelioration in which racial categories can have normative or aspirational force, contributing to positive change.